Racial Sorting and the Emergence of Segregation in American Cities - Shertzer, Allison; Walsh, Randall P. (The Review of Economics and Statistics, 2019)
Residential segregation by race grew sharply during the early twentieth century as black migrants from the South arrived in northern cities. Using newly assembled neighborhood-level data, we provide the first systematic evidence on the impact of prewar population dynamics within cities on the emergence of the American ghetto. Leveraging exogenous changes in neighborhood racial composition, we show that white flight in response to black arrivals was quantitatively large and accelerated between 1900 and 1930. A key implication of our findings is that segregation could have arisen solely from the flight behavior of whites.